Wild edible ectomycorrhizal fungi: an underutilized food resource from the rainforests of Tshopo province (Democratic Republic of the Congo) - Héritier Milenge Kamalebo; André De Kesel (BMC, 2020)
Abstract Background Ectomycorrhizal (EcM) fungi constitute a source of income as well as proper food with considerable nutritional value. Although edible EcM fungi are highly diverse and expected to host considerable nutritional attributes, only few studies focus on their use and promotion in the province of Tshopo (DR Congo). This study provides original ethnomycological and diversity data on edible ectomycorrhizal rainforest fungi from the Man-and-Biosphere reserve of Yangambi and the reserve of Yoko. Methods The list of edible fungi follows the current taxonomy. Taxa were collected in plots situated in different types of rainforests. Each taxon is supported by herbarium reference specimens. Ethnomycological data on locally consumed EcM fungi were collected from randomly selected people living near the Man-and-Biosphere reserve of Yangambi and the Yoko reserve. People were interviewed using a semi-structured questionnaire. The interview campaign involved 160 informants, all randomly selected from 6 different ethnic communities. Results The results reveal that rainforests from the Yangambi Biosphere reserve and Yoko forest reserve provide a relatively high number of edible fungi, more than local people actually use. Mixed forest stands hold the highest diversity in saprotrophic edible fungi (p value < 0.001) while no significant difference (p value > 0.05) was observed in the number of saprotrophic and EcM fungi within monodominant forests. In spite of being accessible, this renewable natural resource is underexploited. Although a wide array of EcM fungi is available in primary forests dominated by ectomycorrhizal trees, local people's major interest goes to the saprotrophic fungi from areas with degraded mixed forests. Conclusion The lack of local interest for EcM fungi is probably related to the considerable distance people have to cover to collect them. As a result, the edible EcM fungi from the Tshopo area represent a potentially interesting but underutilized resource.